Motivation in learning english as foreign language: How Do santri view them? - Suryanto, Bradhiansyah Tri; Izzah, Muhammad Nabil (Universitas Cokroaminoto Palopo, 2024)
This study aimed to students' integrative and instrumental orientations and focuses on knowing the motivation of santri in learning foreign languages at LPBA Nurul Jadid. This study used descriptive qualitative method. The writers used questionnaire and interview as instruments to collect the data. The writers adapted the questionnaire from Gardner’s Attitude, Motivation Test Battery (AMTB) with the integrative and instrumental Scales. The respondents of this study were elementary, intermediate and Advanced level of Lpba nurul jadid student. There were all 90 students. The findings describe that the questionnaire results reveal a consistent trend of disagreement among participants regarding integrative motivation. In contrast, instrumental motivation receives a predominantly positive response. Interviews with representative santris provide additional depth to the findings. The recognition of English as a global language and its practical utility emerges as a significant driving force. Santris express a preference for interactive and enjoyable learning methods, such as games, highlighting the importance of engaging instructional approaches. The results of this study concluded that while challenges exist, the positive reception of instrumental motivation suggests opportunities for educators to leverage practical and utility-focused approaches in English language instruction.